Implementation of CHSE (Cleanliness, Health, Safety, Environment Sustainability) to Gain Consumer Trust at Primebiz Hotel Surabaya - I Dewa Gde Satrya; Jessica Inggita; Mohammad Yusak Anshori (Advances in Global Economics and Business Journal, 2022)
Indonesia has not been spared from the Covid-19 virus outbreak. The presence of this pandemic has impacted all economic activity, including tourism. Currently, Indonesia is adapting to the Covid-19 pandemic by implementing the New Normal. To gain the trust of tourists to vacation during the New Normal, the Ministry of Tourism and Creative Economy (Kemenparekraf) issued a health protocol named CHSE (Cleanliness, Health, Safety, & Environment Sustainability). This protocol is aimed at the tourism sector as well as Indonesia's creative economy which will be operating during the pandemic. However, even though the CHSE protocol has been implemented, many people are still hesitant to return to using hotel facilities. Therefore, this study focuses on examining the implementation of CHSE to regain customer trust during the pandemic. This study used a qualitative method with PrimeBiz Hotel Surabaya as the object of research.